Language of Dramatic Monologue in Poe’s “The Raven” - Dewan, Motikala Subba (Journal of NELTA, 2021)
Dramatic monologue had been used as a powerful tool to express emotions and feelings through the characters in the ancient Greek drama. It received the proper recognition in the Victorian era as a new form of literary device when the various poets and writers started using it in their works. Edgar Allan Poe was not an exceptional. This article explores the language of dramatic monologue in Edgar Allan Poe’s poem “The Raven”. It aims to look at the poem through the three perceptible features of the dramatic monologue: speaker/narrator, audience/listener, and occasion. It examines how the speaker’s soliloquy speech–moaning for the loss of his wife–changes into a powerful dramatic monologue. Obsessed with pain and agony, the speaker’s dramatic monologue escalates finding a listener, ebony raven inside the room. Throughout the poem, the occasion of the cold December becomes the vital point to bestow cryptic feelings to readers. In addition, the article provides an analysis of poetic structures through figurative languages which have made the poem pedagogically rich and their impact has taken the speaker’s dramatic monologue in diﬀerent level.